Internal Communication in Building Organizational Culture at Pasarame Beachwalk Foodcourt - Widianti, Mira Adita; Choirunnisa, Novita (Universitas Pendidikan Nasional, 2023)
This research is motivated by an interesting phenomenon about communication patterns in a Pasarame Beachwalk Foodcourt. Especially to find out internal communication to build organizational culture at the Pasarame Beachwalk food court. Aims to describe and know Internal Communication in building organizational culture (Case study at Pasarame Beachwalk Foodcourt). The approach used by the author is a qualitative research method. Qualitative research methods use in-depth interviews, observation and documentation to participate in collecting data. Internal communication is divided into 2, namely vertical communication, namely communication patterns between superiors and subordinates and horizontal communication, namely communication between fellow staff and divisions or sections. The importance of communication in helping to facilitate work and to align the goals of the members, so that an organized organizational culture is formed in accordance with the vision and mission of the company. Organizational culture has several dimensions, namely Innovation and Risk Taking, Paying Attention to Details, Result Orientation, People Orientation, Team Orientation, Aggressiveness, Stability. Background and technical differences are the main obstacles that often occur. The results of the study show that maintained communication will help members to work more quickly and efficiently. And by maintaining both horizontal and vertical communication can minimize obstacles. From the dimensions of the existing organizational culture, Pasarame Beachwalk tends to have a result-oriented culture and pays close attention to details.